The Quality of Educational Management Systems: Selected Principles from the Qur’an - Usman, Abur Hamdi; Abdullah, Mohd Farid Ravi; Mohamad, Wan Fakhrul Razi Wan (International Journal of Psychosocial Rehabilitation, 2020)
It is increasingly challenging in today’s world to view the education sector as vital and one that should be made a priority in achieving a country’s objectives and visions. The concepts and systems of management are organized and drafted according to modern world standards of development and each country competes to showcase the success of their educational systems. Contemporary management and administration systems constantly refer to the theories established by Western ideals and studies. However, there are still shortcomings in its strategy and modelling. Is this due to the quality of the teachers, the unproductive administration system or the general weakness of the educational management? Through the method of documentation and comprehensive review of literature, this study has found that educational management needs to be managed prudently by its stakeholders. Good quality students are the products of constant refinement and development, the success of which has the potential to secure a country's wellbeing for the current generation as well as the next. Thus, management from the perspective of the Qur’an is seen as the best basis and guiding principle which should be espoused for the national education management strategy.